Wisuda Online di Universitas Hasanuddin: Respon, Makna, dan Perayaan - Zhahnaz Azizah Umar (Emik, 2022)
The graduation ceremony from year to year has not changed much and remains a solemn ceremonial activity that can bring its own euphoria to graduation participants, parents, and other attendees. However, since the Covid-19 pandemic at the beginning of 2020 various changes have occurred, including in the field of education, and one of them is related to the graduation ceremony. In Indonesia, many universities delay graduation, but not a few continue to do it online. This article will discuss online graduation as a substitute for face-to-face graduation due to the current epidemic of Covid-19, so that let alone crowds, physical distance is limited. This study was conducted at Hasanuddin University as one of the universities in Indonesia that carries out online graduation. The study focused on the implementation of the second online graduation, that is, the first period of 2020/2021, conducted between September and November 2021. Data was collected using observation and interviews. Those who participated in this study were graduates of Hasanuddin University (S1) who had attended online graduations, both period IV in 2019/2020 and period I in 2020/2021. There were ten informants who participated in this study. The are varied on the basis of age, place of origin, study program, faculty, and batch. The study indicates that despite the fact that Hasanuddin University is carrying out online graduation due to the Covid-19 outbreak, the graduates felt disappointed because the coveted graduation after more or less four years of studying finally had to be packaged in an online graduation. The meaning of graduation is very diverse, such as some who casually interpret graduation as a formality and euphoria. There are also those who interpret graduation as the result of the struggle for everything they went through while being students, as a transition status and as a space for appreciation. The implementation of online graduation does not have a significant effect on the completion of graduate thesis. Even though during the Covid-19 outbreak would be held online, the graduates are still preparing to take part. This preparation for graduation is divided into three, namely preparations related to media and internet networks, rehearsals, and the graduate appearance. Despite the Covid-19 outbreak, post-graduation celebrations are still carried out. It is argued in this article that Covid-19 is a pandemic, but an epidemic is an epidemic, graduates still intend to carry out various rituals that are carried out such as at offline graduation with various limitations and adjustments to the conditions of the Covid-19 outbreak.